Organizing webinars in UiTMCT setting - general checklist - Abdullah, Nurmuslimah Kamilah; Sulong @ A. Rashid, Ruzaidah; Mohamed Yusoff, Yaumee Hayati; Mohd Isa, Sulaiha; Mohd Fuza, Zatul Iffah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
In March 2020, we were forced to live in a new norm due to the increasing number of Covid-19 cases in Malaysia. The outbreak has also affected tertiary education. The teaching and learning activities dynamically changed, with Online Distance Learning (ODL) rapidly diffused regardless of whether the service providers (lecturers) and customers (students) like it or not. Today, the ODL concept can be applied either in hybrid mode or mixed with hours in physical class.